Dreams for dead bodies: blackness, labor, and the corpus of American detective fiction - Robinson, Michelle (Class : culture, 2016)
Dreams of Dead Bodies: Blackness, Labor, and Detective Fiction in American Literature argues that the detective genre's lineage lies in unexpected texts: experimental works on the margins of what we recognize as classical detective fiction today. It shows that authors like Edgar Allan Poe, Mark Twain, Pauline Hopkins, and Rudolph Fisher drew on detective fiction's puzzle-elements to wrestle with complicated questions about race and labor in the United States, such that the emergence of detective fiction is itself bound to a history of interracial conflicts and labor struggles. Unlike previous studies of detective fiction, this book foregrounds an interracial genealogy of detective fiction, building a nuanced picture of the ways that both black and white American authors appropriated and cultivated literary conventions that finally coalesced in a recognizable genre at the turn of the twentieth century. These authors tinkered with detective fiction's puzzle-elements to address a variety of historical contexts, including the exigencies of chattel slavery, the erosion of working class solidarities by racial and ethnic competition, and accelerated mass production. Dreams for Dead Bodies demonstrates that nineteenth- and early twentieth-century American literature was broadly engaged with detective fiction, and that authors rehearsed and refined its formal elements in literary works typically relegated to the margins of the genre. By looking at these margins, the book argues, we can better understand the origins and cultural functions of American detective fiction.